2004
DOI: 10.2337/diacare.27.7.1623
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes Among Sardinian Children Is Increasing

Abstract: OBJECTIVE -The Sardinian type 1 diabetes register represented the basis to determine the most recent trends and the age distribution of type 1 diabetes incidence among Sardinians Ͻ15 years of age during 1989 . Part of the data (1989 has been already published by the EURODIAB Group with a lower completeness of ascertainment (87%). The geographical distribution of type 1 diabetes risk was also investigated. RESEARCH DESIGN AND METHODS -The new cases of type 1 diabetes in children aged 0 -14 years in Sardinia wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 29 publications
5
55
2
2
Order By: Relevance
“…Within the overweight/obese group, subjects with IGR were also significantly different from NGT subjects, resulting more insulin-resistant and dyslipidemic. Given the high prevalence of autoimmune diabetes in Sardinia [13], we controlled for the presence of GAD and IA2 antibodies in our IGR subjects. The results showed that 2 of the 3 children already with diabetes were affected by autoimmune type 1 diabetes, showing that this condition may also be associated with an overweight/obese phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the overweight/obese group, subjects with IGR were also significantly different from NGT subjects, resulting more insulin-resistant and dyslipidemic. Given the high prevalence of autoimmune diabetes in Sardinia [13], we controlled for the presence of GAD and IA2 antibodies in our IGR subjects. The results showed that 2 of the 3 children already with diabetes were affected by autoimmune type 1 diabetes, showing that this condition may also be associated with an overweight/obese phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of autoimmune type 1 diabetes in Sardinia [13], we evaluated the presence of circulating autoantibodies in the 58 children with IGR. GADA were detectable in 2 of the 3 children affected by diabetes mellitus who had high titres (5.48 and 37.71 U/mL) of circulating GADA associated to high titres (7.53 and 9.28 U/mL) of IA2 autoantibodies, thus confirming a diagnosis of type 1 diabetes.…”
Section: Determination Of Autoantibodies Linked To Type 1 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…30.60, 35.88) of Type 1 diabetes, which is the second highest in the world after Finland [19][20][21][22], and a high prevalence of other autoimmune diseases Type 1 diabetes related, such as Multiple Sclerosis, Celiac Disease, Autoimmune Thyroid Disease and others [23][24][25][26]. For these reasons, Sardinia represents an ideal observatory for investigating genetic and immunological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Sardinia has one of the highest incidences of type 1 diabetes in the world [6], second only to Finland, and a very high prevalence of G6PD deficiency (present in 12-15% of the male population compared with 0.48% in continental Italy) [2]. In Sardinia, all variants of G6PD deficiency are due to the same mutation, which results in only 5-10% residual activity of the enzyme [7] and G6PD deficiency does not show an association with diabetes [8].…”
Section: Introductionmentioning
confidence: 99%